2018
DOI: 10.1002/nau.23509
|View full text |Cite
|
Sign up to set email alerts
|

Demographic features of female urethra length

Abstract: Differences in urethral length in the female population were demonstrated. Thirty percent of patients have atypical urethras that may be a risk factor for sling surgery failure. We therefore postulate introduction of urethral measurement before the procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
21
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 22 publications
3
21
1
1
Order By: Relevance
“…The mean urethral length assessed by a foley catheter was found to resemble that assessed using 3D transperineal ultrasound (3.02 ± 0.41 cm and 3.03 ± 0.34 cm, respectively), suggesting agreement between the two methods. This data is also in line with previous studies reporting a urethral length range of 2‐4 cm measured with introital ultrasound in women with SUI . Also supporting the agreement between the two methods, the ICC obtained suggests excellent accordance (ICC = 0.90) with the standard proposed by Portney et al Moreover, the Bland‐Altman analysis revealed a mean difference close to 0 (−0.01 ± 0.23 cm), showing little to no bias between the two methods.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…The mean urethral length assessed by a foley catheter was found to resemble that assessed using 3D transperineal ultrasound (3.02 ± 0.41 cm and 3.03 ± 0.34 cm, respectively), suggesting agreement between the two methods. This data is also in line with previous studies reporting a urethral length range of 2‐4 cm measured with introital ultrasound in women with SUI . Also supporting the agreement between the two methods, the ICC obtained suggests excellent accordance (ICC = 0.90) with the standard proposed by Portney et al Moreover, the Bland‐Altman analysis revealed a mean difference close to 0 (−0.01 ± 0.23 cm), showing little to no bias between the two methods.…”
Section: Discussionsupporting
confidence: 91%
“…Optimal placement of the material plays an important role in the bulking‐agent efficacy for SUI in women . Given the wide variation in urethral anatomy, mid‐urethral sling efficacy may also be enhanced by optimizing tape location . Physicians often use a foley catheter to evaluate the urethral length and, hence, determine the most suitable injection site or identify the mid‐urethral zone.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Operative reports were reviewed for surgeon description of mesh location at the time of explant. When the surgeon described sling location only in reference to distance from the urethral meatus, the distal urethra was defined as within 1 cm of the meatus, the midurethra was defined as 1 to 3 cm from the meatus, and the proximal urethra/bladder neck (PU/BN) was defined as more than 3 cm from the meatus based on average urethral length of 3 + 0.4 cm . When there was no explicit description of sling location in the operative report sling location was inferred to be midurethral.…”
Section: Methodsmentioning
confidence: 99%